Altruistic behaviors and cooperation among gifted adolescents - Salem, Ashraf Atta M. S.; Abdelsattar, Mahfouz; Abu Al-Diyar, Mosaad; Al-Hwailah, Amthal H.; Derar, Esraa; Al-Hamdan, Nadiah A. H.; Tilwani, Shouket Ahmad (Frontiers in Psychology, 2022)
Cooperation and altruism are frequently studied together or thought to be equivalent constructs. Cooperation occurs when two or more people work together to accomplish a common goal (Tuomela, 1993). Cooperation involves working toward a common goal in which both parties are invested, whereas altruistic behaviors are frequently one-sided and have no overt positive outcome for the party engaging in altruistic behavior. The present study describes the nature of the relationship between cooperation and altruistic behavior in a sample of gifted adolescents in 3 universities in Egypt. It also identified the differences between males/females, and senior students/junior students in both cooperation and altruism. A total of 237 gifted adolescents - with average age 21.3 ± SD 2.6 years- from 3 Egyptian universities in Alexandria, Suez, and Port Said, were involved in this study. Measures used in the study include the Scales for Rating the Behavioral Characteristics of Superior Students (SRBCSS) (Renzulli et al., 2002), Generative Altruism Scale (GAlS) (Büssing et al., 2013), and The Cooperative/Competitive Strategy Scale (CCSS) (Tang (1998). Results revealed that there is a significant positive relationship between altruism and cooperation among gifted adolescents. Also, findings show that there are statistically significant differences between males and females in both altruism and cooperation. In addition, there are differences statistically significant between senior students and junior students in both altruism and cooperation in favor of senior students. It is recommended that altruism and cooperation intervention-based programs should be designed to increase the adaptive behaviors of adolescents.